Distribution of packed lubricant product in Petronas / Razmani Abdul Rahim - Abdul Rahim, Razmani (1989)
Physical Distribution Management has been the subject of an enormous amount of research and development in the past decade resulting in fundamental changes in total stretegy, operational techniques and design of equipment and transport. According to Peter R Attvood in his book, "Planning A Distribution System", physical distribution can cost up to 25 percent or more of the total cost of goods at the point of sale. This is indeed the main catalyst for the growing concern in physical distribution. In the yesteryears, direct labour and production plant cost are the main areas probed in efforts to reduce cost. Nov, progressive firms are directing their attention to the greater economies to be derived from veil-planned and executed warehousing and distribution. Along with this move, there has emerged the need to recognize the wide implication of distribution decisions.